Online Electronic Journals and the Five Laws of Library Science - Khode, Subhash; Khode, Ajay (Journal of Information and Knowledge, 2013)
The advantages of online electronic journals are playing vital roles towards the fulfillment of the five laws of library science. This paper describes how online electronic journals are helpful in successful implementation of the five laws of library science.